2022
DOI: 10.1029/2022gl098545
|View full text |Cite
|
Sign up to set email alerts
|

Complex Coseismic and Postseismic Faulting During the 2021 Northern Thessaly (Greece) Earthquake Sequence Illuminated by InSAR Observations

Abstract: As one of the most seismically active areas in central-northern Greece, Thessaly has been undergoing nearly N-S oriented crustal extension since Late Miocene, forming several prominent basin-and-range landforms such as Tyrnavos basin and Antichasia mountain (Caputo & Pavlides, 1993, Figure 1). Around the primary geologic-tectonic structure, there develop a series of parallel or subparallel synthetic and antithetic normal faults which control the overall tectonic environment of the broader Thessaly area (Figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…The epicentral region of the TES is well monitored instrumentally by an abundance of permanent/temporary seismic and GNSS stations (Figure 2), while InSAR allowed the quantification of the coseismic displacements associated with each of the main events (i.e., Ganas et al., 2021; Papadopoulos et al., 2021). Using a combination of seismological, geodetic and InSAR data, numerous studies attempted to kinematically model the rupture sequence, proposing either a two (Karakostas et al., 2021), a three (Ganas et al., 2021; Kassaras et al., 2022; Papadopoulos et al., 2021) or a four (De Novellis et al., 2021; Yang et al., 2022) fault source model. Despite the differences, all proposed models agree on the geometry and approximate location of the fault that produced the large (M w 6.3) March 3rd earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…The epicentral region of the TES is well monitored instrumentally by an abundance of permanent/temporary seismic and GNSS stations (Figure 2), while InSAR allowed the quantification of the coseismic displacements associated with each of the main events (i.e., Ganas et al., 2021; Papadopoulos et al., 2021). Using a combination of seismological, geodetic and InSAR data, numerous studies attempted to kinematically model the rupture sequence, proposing either a two (Karakostas et al., 2021), a three (Ganas et al., 2021; Kassaras et al., 2022; Papadopoulos et al., 2021) or a four (De Novellis et al., 2021; Yang et al., 2022) fault source model. Despite the differences, all proposed models agree on the geometry and approximate location of the fault that produced the large (M w 6.3) March 3rd earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…The epicentral region of the TES is well monitored instrumentally by an abundance of permanent/temporary seismic and GNSS stations (Figure 2), while InSAR allowed the quantification of the coseismic displacements associated with each of the main events (i.e., Ganas et al, 2021;Papadopoulos et al, 2021). Using a combination of seismological, geodetic and InSAR data, numerous studies attempted to kinematically model the rupture sequence, proposing either a two (Karakostas et al, 2021), a three (Ganas et al, 2021;Kassaras et al, 2022;Papadopoulos et al, 2021) or a four (De Novellis et al, 2021;Yang et al, 2022) fault source model. Despite the differences, all proposed models agree on the geometry and approximate location of the fault that produced the large (M w 6.3) March 3rd earthquake.…”
Section: The Seismotectonics Of the Tesmentioning
confidence: 99%
“…Novellies et al [28] also used InSAR technology to studied this earthquake sequence, and their results confirmed the NE dipping direction of the second event. Yang et.al [3] studied this earthquake sequence using co-seismic and early post-seismic InSAR data. Their results support the NE dipping direction of the second event.…”
Section: Tectonic Settingsmentioning
confidence: 99%
“…Previous researches reported that the well-known and -studied faults in Central Greece did not generate this earthquake sequence [1]. These earthquakes are likely to occur on unmapped or named as blind faults [2,3]. Determining the fault geometry of these blind faults is the significant premise for studying earthquake physics and understanding regional seismogenic mechanism [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation